Bamboo Leaves Extract as Corrosion Inhibitor for Mild Steel - Edyanto, Nur Farzana; Embong, Zaidi; Mohd Jafery, Khawarizmi; Rahim, Maisarah; Mohd Basir, Mohamad Sidiq (Enhanced Knowledge in Sciences and Technology, 2025)
Mild steel is a type of low-carbon steel that is easy to shape and weld, commonly used in construction and manufacturing due to its ductility and malleability. However, corrosion significantly impacts the durability and safety of metals like mild steel. It weakens the material’s strength and ductility, leading to costly repairs. To prevent corrosion, organic inhibitors are used as they not only prevent rust but are also safer for the environment. Bamboo leaves extract (BLE) is an organic and eco-friendly corrosion inhibitor, contains compounds like flavonoids that act as antioxidants and can form a protective layer on metal surfaces, which is can reducing corrosion by inhibiting electrochemical reactions. The objectives of this study are to analyse the effect of bamboo leaves extract (BLE) in preventing corrosion. It begins with immersion tests conducted with four different ratios of NaCL and BLE (100% NaCl, 90 NaCl: 10% BLE, 70 NaCl: 30% BLE and 50% NaCl: 50% BLE). The analysis methods used for chemical property analysis including FTIR, SEM-EDX, and EIS. FTIR analysis was performed to identify functional groups in the bamboo leaves extract, such as hydroxyl groups (O-H), alkanes (C-H), and phenols (C-O). After seven days of immersion, SEM-EDX analysis was conducted on both pre- and post-immersion samples. The pre-immersion analysis showed a clear and smooth mild steel surface, while the post-immersion analysis revealed oxidation and different rate of corrosion on all samples. EIS analysis shows the inhibitors effect of BLE, with Tafel and Nyquist plots showing increased charge transfer resistance (Rct) and reduced double-layer capacitance (Cdl) in BLE-treated samples. The 50% BLE concentration provided the strongest protective layer, resulting in the lowest corrosion rate observed in the Tafel plots. The final results highlight that the solution with 50% NaCl: 50% BLE showed the best performance with the lowest corrosion rate compared to the other ratios.